Effects of dietary sea buckthorn pomace supplementation on skeletal muscle mass and meat quality in lambs. (August 2020) - Qin, Xuze; Zhang, Ting; Cao, Yuxin; Deng, Buhao; Zhang, Jianxin; Zhao, Junxing
Abstract: The aim of the present trial was to evaluate the effects of dietary sea buckthorn pomace (SBP) supplementation on muscle mass, meat nutritional value and quality of lambs. The results showed that dietary 16% SBP supplementation increased muscle mass and altered muscle fiber size distribution. Both nutritional compositions, including crude protein, moisture and ash, and lamb meat quality, including pH, color and cooking loss were not affected by SBP supplementation. Importantly, crude fat content was elevated, and shear force was decreased in Longissimus thoracis (LT) when lambs were fed the SBP containing diet. Moreover, the total antioxidative capacity in LT and the HDL content in serum were elevated in SBP feed lambs. Dietary SBP supplementation increased the Akt/mTOR signaling activity, and downregulated myostatin expression. Taken together, these data suggested that SBP could be used as a feed ingredient for lamb meat production by increasing muscle mass and improving tenderness, water holding capacity and antioxidative capacity of resulting meat.